Perbedaan Hasil Belajar Model Pembelajaran Creative Problem Solving dan Discovery-Inquiry pada Peserta Didik Kelas X - Riski Nur Istiqomah Dinnullah; Khumairoh Lailatul Fadilah; Yuniar Ika Putri Pranyata (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2021)
Finding differences in learning outcomes between the Creative Problem Solving (CPS) model and the Discovery-Inquiry model is the goal of the research. The low student learning outcomes due to their inability to participate in learning activities are the things that underlie the research objectives. The model in this study emphasizes the enthusiasm of students in solving problems. Purposive Sampling technique is used in the selection of research classes by providing the same learning material. The data was obtained from the validity test and the reliability test was obtained from the instrument test. Then the normality test, homogeneity test, and hypothesis testing were carried out in the process of analyzing research data. The results obtained with a significance value of less than 0.05, namely 0.017. This shows that there are differences in learning outcomes between the Creative Problem Solving (CPS) model and the Discovery-Inquiry model for class X students which coincided at SMA Negeri 1 Kutorejo in the 2019/2020 school year. Another difference is also seen in the class average score. In the Discovery-Inquiry class the average score is 71.78, while in the Creative Problem Solving (CPS) class the average value is84.22. Some of these things are enough to prove that compared to the Discovery-Inquiry model, it is better to apply the Creative Problem Solving (CPS) model.